2017
DOI: 10.5414/cn108901
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic microangiopathy associated with cetuximab, an epidermal growth factor receptor inhibitor

Abstract: Cetuximab is a chimeric human-murine monoclonal antibody that binds competitively and with high affinity to the epidermal growth factor receptor (EGFR) and is used to treat advanced squamous cell carcinoma of the head and neck. After receiving a total of six doses of cetuximab, a 72-year-old male presented with pretibial edema, acne-like skin rash, and nephrotic syndrome. The renal biopsy findings revealed features of thrombotic microangiopathy (TMA), with the expansion of the subendothelial zone, reduplicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the literature, only 5 cases of NS due to cetuximab and panitumumab have been reported. [5][6][7][8][9] Nephrotic syndrome developed with cetuximab in 4 cases and panitumumab in 1 case. The characteristics of these patients were summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, only 5 cases of NS due to cetuximab and panitumumab have been reported. [5][6][7][8][9] Nephrotic syndrome developed with cetuximab in 4 cases and panitumumab in 1 case. The characteristics of these patients were summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicopathological features of glomerular diseases associated with anti-EGFR monoclonal antibody in cancer patients [5][6][7][8][9]. …”
mentioning
confidence: 99%
“…Unlike this case, our patient's renal function did not improve after 4 weeks of immunosuppressive therapy. Koizumi et al [ 9 ] reported a kidney biopsy with glomerular features of TMA due to cetuximab administration. Administration of cetuximab was discontinued and, nine weeks after the discontinuation of cetuximab, the proteinuria decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there were reported cases of AKIs and nephrotic syndromes in patients treated with cetuximab. Histopathological findings in these cases included crescentic diffuse proliferative glomerulonephritis [ 121 ], diffuse proliferative glomerulonephritis [ 122 ] and TMA [ 123 ].…”
Section: Tumor-targeting Monoclonal Antibodies (Tt-mabs)mentioning
confidence: 99%